Assessing the feasibility and efficacy of written benefit-finding for caregivers of children with autism: a pilot study. Issue 1 (2nd January 2016) - Lovell, Brian; Moss, Mark; Wetherell, Mark A.
Abstract : Written emotional disclosure (WED), a time and cost effective intervention that can run in participants' homes, might be especially well suited for autism caregivers. This study assessed the effectiveness of directed written disclosure for coping with the stress of caring for a child with autism. 37 caregivers of children with autism wrote for 20 minutes on three days about: (1) the benefits of caregiving or (2) a control topic while at home. Anxiety and depression were assessed at baseline, one month and three months post writing. Data indicated that anxiety scores for caregivers in the benefit finding condition were less likely to fall within the clinical range at three months post writing. However, group differences in anxiety from baseline reflected deterioration in controls rather than palliative effects in the benefit finding group. In conclusion, written benefit finding might be effective for buffering against the psychological sequelae associated with caregiving stress.